Концептуализация вращательного движения в русском и польском языках - Narloch, Andrzej (Acta Polono-Ruthenica, 2017)
In recent years, linguistic studies have laid great emphasis on the semantic side of linguistic expressions. The subject of this paper is an attempt to introduce the term of “circular motion” in common verb patterns and set phrases in Russian and Polish. The description concerns the problem of creating metaphors based on circular motion verbs. The paper distinguishes between four metaphor types which have been presented by the comparative method between Russian and Polish.